Evaluation of bacterial biofilm, smear layer, and debris removal efficacy of a hydro-dynamic cavitation system with physiological saline using a new ex vivo model: a CLSM and SEM study - He Liu; Xi Wang; Zhejun Wang; Ya Shen (BMC Oral Health)
Abstract Introduction To evaluate the bacterial biofilm, smear layer and debris removal efficacy of a hydro-dynamic cavitation system with physiological saline using a new ex vivo model. Methods Seventy-five dentin discs were prepared from fifty-four extracted teeth. Seventy-five artificial root sockets were prepared. Sixty dentin discs were used to grow 3-week-old bacterial biofilms, while smear layer and debris were produced on fifteen dentin discs. These dentin discs were adhered to the middle third of the artificial root canals. The sixty ex vivo models with biofilm-covered dentin discs were divided into six groups: control, needle with physiological saline, ultrasonic with physiological saline, Odne™ Clean with physiological saline, needle with 3% NaOCl, and ultrasonic with 3% NaOCl. Biofilm removal efficacy was evaluated using confocal laser scanning microscopy. The fifteen ex vivo models with smear layer and debris-covered dentin discs were divided into three groups: control, Odne™ Clean with physiological saline, and 5% NaOCl followed by 17% EDTA. Smear layer and debris removal efficacy was evaluated using scanning electron microscopy. Statistical analysis was performed using one-way analysis of variance for comparisons involving more than two groups. Post-hoc pairwise comparisons were conducted using the Tukey test. Results OdneTMClean with physiological saline (98%) performed significantly better than needle irrigation (47%) or ultrasonic activation (54%) with physiological saline (P < 0.05). OdneTMClean with physiological saline removed biofilms as effectively as needle irrigation (97%) or ultrasonic activation (98%) with 3% NaOCl (P > 0.05). Additionally, 5% NaOCl followed by 17% EDTA (score: 1.33) removed the smear layer significantly better than OdneTMClean with physiological saline (score: 4.47) (P < 0.05). However, OdneTMClean with physiological saline (score: 1.27) removed debris as effectively as 5% NaOCl followed by 17% EDTA (score: 1.13) (P > 0.05). Conclusions OdneTMClean with physiological saline can effectively remove bacterial biofilm and debris from the dentin surface but cannot effectively remove the smear layer. Utilizing OdneTMClean during the final irrigation may enhance root canal cleaning efficacy.